2022
DOI: 10.3390/life12091409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Doses of Vitamin D on the Intestinal Flora of Babies with Eczema: An Experimental Study

Abstract: Infantile eczema is a common allergic disease caused by a variety of factors, which is often accompanied by immune dysfunction and dysbiosis of the intestinal flora. Vitamin D may affect the composition and function of intestinal flora by regulating the expression of antimicrobial peptides, thereby avoiding intestinal dysbiosis. The present study aims to explore whether the disorder of intestinal flora and immune function can be reversed by changing the Vit D intake of eczema infants. In this study, 12 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…Vitamin D increased the microbial diversity and richness and showed a significant beta diversity [36,37,40,43]. On the contrary, a study in infants with eczema showed a significant low microbial diversity with high doses of Vitamin D but had similarities between the low-Vitamin D-supplemented group and healthy infants [40]. A positive association with the infant gut microbial community with Vitamin D status was observed in some of these studies.…”
Section: Association Of Vitamin D With Microbial Composition and Dive...mentioning
confidence: 84%
See 4 more Smart Citations
“…Vitamin D increased the microbial diversity and richness and showed a significant beta diversity [36,37,40,43]. On the contrary, a study in infants with eczema showed a significant low microbial diversity with high doses of Vitamin D but had similarities between the low-Vitamin D-supplemented group and healthy infants [40]. A positive association with the infant gut microbial community with Vitamin D status was observed in some of these studies.…”
Section: Association Of Vitamin D With Microbial Composition and Dive...mentioning
confidence: 84%
“…Two of these studies containing exclusively breast-fed infants showed a relation between Vitamin D supplementation and alpha and beta diversity. Vitamin D increased the microbial diversity and richness and showed a significant beta diversity [36,37,40,43]. On the contrary, a study in infants with eczema showed a significant low microbial diversity with high doses of Vitamin D but had similarities between the low-Vitamin D-supplemented group and healthy infants [40].…”
Section: Association Of Vitamin D With Microbial Composition and Dive...mentioning
confidence: 90%
See 3 more Smart Citations